A Theological Comparative Exploration of Tolerance in Islam and Buddhism - Ramli, Ahmad Faizuddin; Ashath, Mohamed (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
Religious tolerance is a fundamental ethical principle in both Islam and Buddhism, shaping interfaith relations, governance models, and societal harmony. While both traditions emphasize compassion, patience, and mutual respect, their doctrinal foundations of tolerance differ significantly. Islamic tolerance (tasāmuḥ) is rooted in Islamic monotheism (tawḥīd), divine law (sharīʿah) and prophetic teachings (ḥadīth), where interfaith coexistence is structured within legal and ethical frameworks. The Qur’an (2:256) affirms that “there is no compulsion in religion,” and historical precedents such as the Constitution of Medina institutionalized protections for religious minorities. Conversely, Buddhist tolerance (kṣānti) arises from a nontheistic spiritual path in which moral conduct is governed by karma rather than by divine commandments. Buddhism fosters patience and forbearance as essential virtues in the Bodhisattva ideal and meditative disciplines, emphasizing inner transformation rather than legal enforcement. By analyzing both primary religious texts and contemporary sources, this study highlights common values between Islam and Buddhism, advocating for deeper interfaith dialogue and academic research on universal principles of tolerance. Understanding Islamic and Buddhist tolerance offers valuable frameworks for fostering religious harmony and coexistence in a diverse world.